1985
DOI: 10.2466/pr0.1985.57.3f.1079
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Study of the Hierarchical Structure of Human Relationships

Abstract: A theoretical hierachy of human relationships is constructed in terms of altruism. It is hypothesized that the probability for an actor A to perform an altruistic act to a person B depends on the relationship between A and B, and the probability decreases consistently in the following order of relationships: close relatives, best friends, strangers who are very weak or very young or who are elite in society, common strangers, and enemies. Two hypothetical moral dilemmas were used to study the hierarchy and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 3 publications
1
17
2
Order By: Relevance
“…On the contrary, there was a trend towards homogeneity in moral reasoning scores among the different age groups. The present study does not support the claim that stages 2, 3, and 4 responses decrease with age, while stages 5A, 5B, and 6 (P%) increase as participants become older (Ma, 1985;Park & Johnson, 1984). The results related to age are inconsistent with the findings of Ruegger and King (1992) who found that students over the age of 40 were more ethical than were younger students.…”
Section: Effects Of Age On Moral Reasoningcontrasting
confidence: 82%
“…On the contrary, there was a trend towards homogeneity in moral reasoning scores among the different age groups. The present study does not support the claim that stages 2, 3, and 4 responses decrease with age, while stages 5A, 5B, and 6 (P%) increase as participants become older (Ma, 1985;Park & Johnson, 1984). The results related to age are inconsistent with the findings of Ruegger and King (1992) who found that students over the age of 40 were more ethical than were younger students.…”
Section: Effects Of Age On Moral Reasoningcontrasting
confidence: 82%
“…A plot of these unrotated factor loadings would give a semicircular configuration. According to Davison ( 1977) and Ma (1985), the present results support a hierarchical structure underlying each of the two sets of ratings. The general results provide clear support for Hypotheses 1 and 2, as well as for the proposed hierarchy of human relationships in children.…”
supporting
confidence: 80%
“…The present study differs from Ma's (1985Ma's ( , 1989 previous studies in two major aspects. First, in Ma's previous studies, a set of relationship indexes were formulated by averaging subjects' ratings of the group of people concerned in two hypothetical dilemmas, The Sinking Boat and Car Accident.…”
Section: Hypothesescontrasting
confidence: 68%
See 2 more Smart Citations